0362 The Cost of In-Person versus Telehealth PAP Initiation for Patients with Sleep Apnea. (25th May 2022) - Jambulingam, Nikita; Sarmiento, Kathleen; Gomez, Alexander; Smith, Connor; Mitchell, Michael; Lee, Diane; Sanders, Elizabeth; Ryden, Armand; Martin, Jennifer; Zeidler, Michelle
Abstract: Introduction: Telehealth has been widely integrated into healthcare systems during the COVID-19 pandemic and is likely to remain a part of routine clinical care. At the VA Greater Los Angeles Healthcare System (VAGLAHS), positive airway pressure (PAP) set-up visits transitioned from in person to telehealth for newly diagnosed sleep apnea patients during the pandemic. The telehealth pathway included mailing of PAP machines to patients with follow-up video/phone education by respiratory therapists (RTs). As part of a larger study examining the clinical outcomes resulting from telehealth versus in-person PAP initiation, we performed a cost analysis of these two treatment pathways within VAGLAHS. Methods: We examined the total variable direct cost of telehealth versus in-person PAP initiation for patients newly diagnosed with sleep apnea at VAGLAHS between March and October 2021 (n = 2, 662 PAP set-ups) using a bottom-up analysis. There was an average of 16 PAP set-ups per day with 11 set-ups (68.7%) via telehealth and 5 set-ups (31.3%) in person. Results: The total variable direct cost of telehealth PAP initiation was 98.87 per patient. The total variable direct cost of in-person PAP initiation was 50.58 per patient. For telehealth, there was an additional cost of mailing the PAP machine and 31.2% more RT time spent on educating patients compared to the in-person pathway. After the initial PAP set-up visit, a larger subset of patients required additional troubleshooting help from RTs about proper PAP use after telehealth compared to in-person set-ups (5% versus 1%). Conclusion: The telehealth PAP initiation pathway was nearly two times the cost of in-person PAP initiation. This resulted from the additional cost of mailing the PAP machine, more RT time spent on education, and a greater need for troubleshooting after the visit. Telehealth visits may need to be supplemented by written educational materials or web-based resources to reduce the need for additional support after the initial visit. Support (If Any): OCC study funding, VAGLAHS GRECC